Influence of gender and academic program on financial literacy among Malaysian university students - Hawati Janor,; Nurul Fareena Jasli,; Rubayah Yakob,; Noor Azuan Hashim, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2016)
This study examines financial literacy among Malaysian university students. It is conducted among undergraduate students at the Universiti Kebangsaan Malaysia. It also examines the effect of gender and different academic program on FL level. Various test such as the Independence T-test, ANOVA and Tukey Honest Significant Difference HSD are employed on 300 samples of primary data collected using questionnaires distributed among students from selected faculties. The questionnaire contains questions among others on financial attitude, knowledge as well personal characteristics items. The results show that the level of FL among UKM students is moderate. From the Independent T-Test, the results show a significant difference in FL scores for males and females which suggest that males are more financially literate than females. From the ANOVA and Tukey HSD the study finds that there is a statistically significant different between type of majoring and FL level with business majoring students have higher level of FL when compared to non-business majoring. From the business majoring, Financial Services and Risk Management specialization has the highest FL level. It is therefore recommended that a comprehensive and aggressive program of financial education be carried out among young people in Malaysia especially to university students from all academic program.